2018
DOI: 10.3390/su10124359
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Traffic Congestion on Urban Expressways Considering Drivers’ Unreasonable Behavior at Merge/Diverge Sections in China

Abstract: The mechanisms of traffic congestion generation are more than complicated, due to complex geometric road designs and complicated driving behavior at urban expressways in China. We employ a cell transmission model (CTM) to simulate the traffic flow spatiotemporal evolution process along the expressway, and reveal the characteristics of traffic congestion occurrence and propagation. Here, we apply the variable-length-cell CTM to adapt the complicated road geometry and configuration, and propose the merge section… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…В роботі [29] досліджений механізм утворення заторів на автомагістралях Китаю. Разом з тим дослідження, що стосуються змінювання стану водія в цій роботі не наведено.…”
Section: аналіз останніх досліджень і публікаційunclassified
“…В роботі [29] досліджений механізм утворення заторів на автомагістралях Китаю. Разом з тим дослідження, що стосуються змінювання стану водія в цій роботі не наведено.…”
Section: аналіз останніх досліджень і публікаційunclassified
“…Authors of work [8] investigated and showed a mechanism of the formation of traffic jams on China's highways. However, there were no studies related to changes in a driver's state.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Formulas (8) and (9) for the assessment of the probability of an accident at sections of a transport network and at transport nodal points with an individual traffic participant considering model (10)…”
Section: Assessment Of the Probability Of An Accident With An Indimentioning
confidence: 99%
“…Compared with urban traffic congestion, there are fewer studies that focus on traffic congestion in expressways. The existing studies are based on different data and methods to investigate traffic congestion in expressways [30][31][32][33][34][35][36][37][38][39][40] and analyze the characteristics of traffic congestion in expressways [41][42][43][44][45]. The summary of representative studies about traffic congestion in expressways is listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%